Antimycobacterial activity of pyrazinoate prodrugs in replicating and non-replicating Mycobacterium tuberculosis. (July 2016) - Segretti, Natanael Dante; Simões, Cristina Kortstee; Corrêa, Michelle Fidelis; Felli, Veni Maria Andres; Miyata, Marcelo; Cho, Sang Hyun; Franzblau, Scott Gary; Fernandes, João Paulo dos Santos
Summary: Tuberculosis (TB) is an important infectious disease caused by Mycobacterium tuberculosis (Mtb) and responsible for thousands of deaths every year. Although there are antimycobacterial drugs available in therapeutics, just few new chemical entities have reached clinical trials, and in fact, since introduction of rifampin only two important drugs had reached the market. Pyrazinoic acid (POA), the active agent of pyrazinamide, has been explored through prodrug approach to achieve novel molecules with anti-Mtb activity, however, there is no activity evaluation of these molecules against non-replicating Mtb until the present. Additionally, pharmacokinetic must be preliminary evaluated to avoid future problems during clinical trials. In this paper, we have presented six POA esters as prodrugs in order to evaluate their anti-Mtb activity in replicating and non-replicating Mtb, and these showed activity highly influenced by medium composition (especially by albumin). Lipophilicity seems to play the main role in the activity, possibly due to controlling membrane passage. Novel duplicated prodrugs of POA were also described, presenting interesting activity. Cytotoxicity of these prodrugs set was also evaluated, and these showed no important cytotoxic profile.